Fostering Learner Autonomy by using Moodle as Pedagogical Tool: Reflections on Students’ Perceptions - Neupane, Arjun (Interdisciplinary Research in Education, 2019)
Moodle is an open source for e-learning system. It is as a tool for delivering contents to students and it is useful to build rich collaborative learning communities. It allows users to be active learners, who actively participate in the online learning process. Based on this background, this study aimed to investigate the students’ views on the use of Moodle in mathematics education. This study gave attention to the variables of perceived usefulness, perceived ease of use, attitude and students’ self- efficacy in learning mathematics. Participants of this study consisted of 24 students, who took first and second semester courses at the master's level in Mathematics Education in 2018 batch from Open and Distance Education Center (ODEC), TU. There are 21 male and three female students. Four students were chosen for the interview including one female representative. Data triangulation between the data of interviews, online observation, and interviews with online teachers was used to analyze and analysis of the data. Three online teachers were chosen for interview purposively. The finding revealed that students had a positive perception towards the use of Moodle and were happy to learn mathematics from the online mode rather than the face-to-face mode. It is suggested that the Moodle if used appropriately and systematically, benefits tutors and students equally.